식미 관능평가 5가지 방법별 전문가와 일반인의 평가능력 비교 - 윤미라; Mi-ra Yoon; 곽지은; Jieun Kwak; 이정희; Jeong-heui Lee; 전재범; Jaebuhm Chun; 박향미; Hyang-mee Park; 서정필; Jung-pil Suh; et al. (Korean journal of crop science, 2016)
This experiment aimed to compare the sensory ability of experts and untrained to evaluate three rice varieties by using five sensory evaluation methods. All panelists showed significant differences in their sensory abilities to distinguish among Haiami, Chucheong, and Dasan 1 rice varieties when using the duo-trio test and triangle test. The expert panelists showed a clear preference in the following order: Haiami > Chucheong > Dasan 1, when using the paired comparison test, ranking test, and multiple comparison test. However, the untrained panelists showed no significant differences in their sensory ability to distinguish between the Haiami and Chucheong varieties when using the multiple comparison test. The results indicate that, for sensory evaluation of cooked rice by untrained panelists, the paired comparison test is suitable for evaluating two samples and the ranking test is suitable for evaluating more than two samples.